Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.47793/hp.815185
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Association Between Loneliness, Social Skill Levels and Internet Addiction in Junior High School Students’

Abstract: Aim: This study was conducted to investigate the association between internet addiction(IA), and social skills and loneliness levels in junior high school students and to determine the factors affecting their IA levels. Method: The population of the study consisted of students attending junior high schools in Kirklareli, in the 2017-2018 academic year(N=10,682).After minimum sample size was calculated as 668, 693 students were reached. In the study, the Internet Addiction Scale(IAS), Matson Evaluation and Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…İnternete telefonla bağlanmanın sağladığı kolaylıklar neticesinde internet bağımlılığına olan eğilimi arttırması (Derin, 2013) ve kendine ait cep telefonu bulunan ve cep telefonunda internet bağlantısı olan ortaokul öğrencilerin internet bağımlılık puanlarının daha yüksek bulunması (Kısa, 2018) cep telefonunun internet bağlılığı oluşmasında etkili olabileceğini düşündürmektedir.…”
Section: İnternet Bağımlılığı Kavramıunclassified
See 1 more Smart Citation
“…İnternete telefonla bağlanmanın sağladığı kolaylıklar neticesinde internet bağımlılığına olan eğilimi arttırması (Derin, 2013) ve kendine ait cep telefonu bulunan ve cep telefonunda internet bağlantısı olan ortaokul öğrencilerin internet bağımlılık puanlarının daha yüksek bulunması (Kısa, 2018) cep telefonunun internet bağlılığı oluşmasında etkili olabileceğini düşündürmektedir.…”
Section: İnternet Bağımlılığı Kavramıunclassified
“…Ortaokul ve lise öğrencilerinde (ergenlerde) internet bağımlılığı ve akademik başarı arasındaki ilişkinin değerlendirildiği bazı çalışmalarda, düşük eğitim seviyesi ile düşük akademik başarının yüksek internet bağımlığına (Esen ve Siyez, 2011;Yıldız, ve diğ., 2018), aşırı eğlence amaçlı internet kullanımının akademik başarısızlığa (Kısa, 2018) ve okul başarısının internet bağımlılığında azalmaya (Akgül, 2016) ve neden olduğu sonucuna varılmıştır.…”
Section: Sonuç Ve öNerilerunclassified
“…Several scholars have also observed that students' social skill scores do not differ according to the grade level. These findings can be explained by the fact that the participant students' ages did not vary significantly (Ayhan Bostancı, 2020;Kısa, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Based on these findings of the study, it can be concluded that as the internet and game addiction scores of gifted children increase, their interpersonal skills, self-management, academic skills and social competencies, which are important components of school social competence, weaken. Previous studies have also found a negative relationship between computer addiction and social skills (Ayhan Bostancı, 2020;Caplan, 2005;Çeliker, 2020;Kısa, 2018), which can be caused by the fact that children who already have problems with their social skills tend to use the internet and play games more. Gifted children not only think differently but also feel different (Silverman, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation